Dr. Benjamin Vierling House - (:unkn) unknown (Wake Forest University)
From: A Short History of Forsyth's Medical Past by Robert Prichard. 1981. Slide 15.
Dr. Benjamin Vierling came to Salem on February 22, 1790 and practiced medicine there for 27 years before his death in 1817. In 1802, Vierling built a large house at the end of Bank Street. After restoration his home and barn are now part of Old Salem’s tour.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth